Differential Effects of Visual-Acoustic Biofeedback Intervention for Residual Speech Errors - McAllister Byun, Tara; Campbell, Heather (Frontiers in Human Neuroscience, 2016)
Recent evidence suggests that the incorporation of visual biofeedback technologies may enhance response to treatment in individuals with residual speech errors. However, there is a need for controlled research systematically comparing biofeedback versus non-biofeedback intervention approaches. This study implemented a single-subject experimental design with a crossover component to investigate the relative efficacy of visual-acoustic biofeedback and traditional articulatory treatment for residual rhotic errors. Eleven child/adolescent participants received ten sessions of visual-acoustic biofeedback and ten sessions of traditional treatment, with the order of biofeedback and traditional phases counterbalanced across participants. Probe measures eliciting untreated rhotic words were administered in at least 3 sessions prior to the start of treatment (baseline), between the two treatment phases (midpoint), and after treatment ended (maintenance), as well as before and after each treatment session. Perceptual accuracy of rhotic production was assessed by outside listeners in a blinded, randomized fashion. Results were analyzed using a combination of visual inspection of treatment trajectories, individual effect sizes, and logistic mixed-effects regression. Effect sizes and visual inspection revealed that participants could be divided into categories of strong responders (n=4), mixed/moderate responders (n=3), and non-responders (n=4). Individual results did not reveal a reliable pattern of stronger performance in biofeedback versus traditional blocks, or vice versa. Moreover, biofeedback versus traditional treatment was not a significant predictor of accuracy in the logistic mixed-effects model examining all within-treatment word probes. However, the interaction between treatment condition and treatment order was significant: biofeedback was more effective than traditional treatment in the first phase of treatment, and traditional treatment was more effective than biofeedback in the second phase. This is consistent with existing theory and data suggesting that detailed knowledge of performance feedback is most effective in the early stages of motor learning. Further research is needed to confirm that an initial phase of biofeedback has a facilitative effect, and to determine the optimal duration of biofeedback treatment. In addition, there is a strong need for correlational studies to examine which individuals with residual speech errors are most likely to respond to treatment.